Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Synthesis of Si-MCM-41 from ternary SiO2-CTAOH-H2O system via dry gel conversion route - Taralkar, U. S.; Niphadkar, P. S.; Joshi, P. N. (Journal of Sol-Gel Science and Technology, 2009)
Steam assisted dry gel conversion method was employed for the synthesis of Si-MCM-41 from ternary SiO2:CTAOH:H2O systems wherein fumed silica was used as a source of silica. The influence of synthesis time, molar ratios of CTAOH/SiO2 in dry gel and the water content at the bottom of autoclave on the quality and formation of mesophases has been investigated. Powder XRD, N-2 adsorption-desorption, TEM and hydrothermal stability test were the techniques used for sample characterization. Keeping molar ratio of CTAOH/SiO2 constant, shorter synthesis time, lower unit cell parameter and d spacing were observed when steam assisted dry gel conversion method was employed in place of conventional hydrothermal method. There exists an optimum lower limit for water content at the bottom of autoclave for reducing the synthesis period. Keeping synthesis temperature and CTAOH/SiO2 molar ratio fixed, Si-MCM-41 with improved hydrothermal stability was obtained by steam assisted dry gel conversion route.
Keywords: Dry gel conversion; powder diffraction; Si-MCM-41; Sol-gel growth; Structural stability; Textural properties

Synthesis, characterization and photocatalytic behavior of TiO2-SiO2 mesoporous composites in hydrogen generation from water splitting - Niphadkar, P. S.; Chitale, S. K.; Sonar, S. K.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Journal of Materials Science, 2014)
TiO2-SiO2 mesoporous composite photocatalysts with different proportions (in wt%) of TiO2 and SiO2 (TiO2-SiO2 = 20:80, 40:60, 60:40, 80:20 and 100:0) were prepared by loading TiO2 on as-synthesized Si-MCM-41 using sol-gel method. The physicochemical properties of composites were investigated by powder X-ray diffraction, N-2 adsorption-desorption measurements, transmission electron microscopy and UV-Vis diffuse reflectance spectroscopy. It is revealed that the titanium species are dispersed as TiO2 having interaction with the surface of the support. Even at high TiO2 loading, the mesostructural feature of MCM-41 was found to be intact without pore blockages. The change in morphology of TiO2 particle was observed with increase in TiO2 loading which may be due to different environment for the growth of TiO2. The photocatalytic evaluation of composites was carried out in production of hydrogen by water splitting. Among the prepared samples, mesoporous composite containing 60 % TiO2 (MTi60) has shown the best results (0.08805 mmol of H-2/h/g of TiO2) compared to other composite photocatalysts. The catalytic performance of this sample was further enhanced (similar to 8 times) after loading 1 % Pt in water splitting (0.70161 mmol of H-2/h/g of TiO2). 1 % Pt loaded on pure TiO2 (MTi100) showed hydrogen evolution of the magnitude 0.26 mmol of H-2/h/g of TiO2. TiO2-SiO2 mesoporous composite photocatalyst showed much higher activity (similar to 1.9 times) than amorphous silica-embedded titania catalyst having same composition.

Synthesis of Sn-containing anatase (TiO2) by sol-gel method and their performance in catalytic water splitting under visible light as a function of tin content - Tangale, N. P.; Niphadkar, P. S.; Samuel, V.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Materials Letters, 2016)
Sol-gel route was employed to prepare a series of Sn-containing anatase with different molar (Ti/Sn) ratios ranging from 49 to 1. Samples were characterized by powder XRD, UV-vis, XPS, SEM, EDAX, low temperature N-2 sorption technique and Raman Spectroscopy. Except anatase phase, no other crystalline phase was observed when Ti/Sn molar ratio was varied from 49 to 9 and for Sn free sample. However, further decrease in the ratio lead to the appearance of additional SnO2 phase whose peak intensities were increased with the increase in the tin content. Irrespective of tin content, all samples showed red-shift in UV-vis spectra. Moreover, samples showed Raman shift to higher vibration side from 143 cm(-1) to 147 cm(-1) indicating the doping of Sn2+ into TiO2. By virtue of low band gap, anatase crystallite size and an absence of XRD visible SnO2, ST (19) has shown maximum photocatalytic activity upon 1 wt% Pt loading. It has exhibited the highest rate (0.1264 mmole/g/h) for visible light induced hydrogen evolution by water splitting. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Sn2+ doped titania; SnO2/TiO2; Sol-gel preparation; visible light; water splitting